S-Ketamine Reduces the Risk of Rebound Pain in Patients Following Total Knee Arthroplasty: A Randomized Controlled Trial - Li Q; Tian S; Zhang L; Chai D; Liu J; Sheng F; Jiang X; Feng W; Zhao Y; Zhu Y (Drug Design, Development and Therapy)
Qun Li,1,* Shaoqi Tian,2,* Lei Zhang,1 Dongyue Chai,1 Jia Liu,1 Fang Sheng,1 Xin Jiang,3 Wei Feng,1 Yang Zhao,1 Youzhuang Zhu1 1Department of Anesthesiology, Shandong Provincial Key Medical and Health Laboratory of Anesthesia and Brain Function, The Affiliated Hospital of Qingdao University, Qingdao, Shandong Province, 266000 People’s Republic of China; 2Department of Joint Surgery, The Affiliated Hospital of Qingdao University, Qingdao, Shandong Province, 266000, People’s Republic of China; 3Phase I Clinical Trial Center, The Affiliated Hospital of Qingdao University, Qingdao, Shandong Province 266000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yang Zhao; Youzhuang Zhu, Department of Anesthesiology, Shandong Provincial Key Medical and Health Laboratory of Anesthesia and Brain Function, The Affiliated Hospital of Qingdao University, Qingdao, Shandong Province, 266000, People’s Republic of China, Tel +860532-82919392, Email zhaoy1979@qdu.edu.cn; youzhuang_zhu@qdu.edu.cnPurpose: Investigating the effectiveness of S-ketamine in reducing rebound pain (RP) following total knee arthroplasty.Patients and Methods: This study was a randomized, double-blind, placebo-controlled trial involving 356 adult patients undergoing total knee arthroplasty. Patient enrollment occurred between April and October 2023, with in-person follow-up assessments conducted from admission to 3 days post-surgery. Participants were randomly assigned to the S-ketamine group (n = 178) and the placebo group (n = 178). In the S-ketamine group, participants received a continuous intraoperative infusion of S-ketamine at a dose of 0.30 mg/(kg·h) from the completion of spinal anesthesia until the beginning of joint cavity closure, whereas the placebo group received a continuous infusion of 0.9% saline at the same volume and duration. The primary outcome was the incidence of RP within 12 hours post-surgery. Secondary outcomes included the incidence of RP within 24 hours, time to RP onset, time to first rescue analgesia, pain scores, opioid consumption, clinical outcomes, and harms.Results: RP was observed in 21.3% of patients in the S-ketamine group compared with 34.8% in the placebo group within 12 hours post-surgery (adjusted RR, 0.62; 95% CI, 0.44 to 0.88; P = 0.008). The onset of RP was significantly delayed in the S-ketamine group compared with the placebo group (unadjusted HR, 0.60; 95% CI, 0.41 to 0.88; P = 0.009). The numerical rating scale during activity and physical therapy was lower in the S-ketamine group than in the placebo group (day 1 AM: unadjusted difference, − 1; 95% CI, − 1 to 0; P = 0.011; day 1 PM: unadjusted difference, − 1; 95% CI, − 1 to 0; P = 0.003; day 1 physical therapy: unadjusted difference, − 2; 95% CI, − 2 to − 1; P < 0.001). The quality of recovery score was higher in the S-ketamine group than in the placebo group (unadjusted difference, 5; 95% CI, 5 to 5; P < 0.001). Patient satisfaction was higher in the S-ketamine group than in the placebo group (unadjusted difference, 1; 95% CI, 1 to 1; P < 0.001).Conclusions: S-ketamine effectively reduces the risk of rebound pain and delays its onset in total knee arthroplasty. Additionally, S-ketamine can reduce early pain levels, enhance recovery quality, and improve patient satisfaction.Keywords: S-ketamine, rebound pain, total knee arthroplasty, nerve block